(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: Identify some factors related to diarrhea after using antibiotics. Methods: A cross-sectional descriptive study with 236 children under 6 years of age with diarrhea after taking antibiotics treatment at the National Children’s Hospital from October 2017 to September 2018. Results: Common age is 7-24 months. The main antibiotic used is Cephalosporin. The time to end diarrhea symptoms was different between the group with and without inpatient treatment at the primary level (p<0.05). The mean duration to end diarrhea symptoms significant associated with groups with other infections (p<0.05). Conclusion: The duration of diarrhea symptoms associated with the history of treatment at the primary level and associated infection groups.